1999
DOI: 10.2337/diacare.22.5.700
|View full text |Cite
|
Sign up to set email alerts
|

Risk for metabolic control problems in minority youth with diabetes.

Abstract: These results underscore and quantify the increased risk for glycemic control problems of lower-income, black children with diabetes. In the absence of effective intervention, these youths are likely to be overrepresented in the health care system as a result of increased health complications related to diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
109
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(120 citation statements)
references
References 4 publications
10
109
0
1
Order By: Relevance
“…Previous intervention research was conducted with primarily white, middle-class samples and therefore did not address the needs of minority and/or low-income adolescents with diabetes. This is an important gap in the literature, because minority subjects are more likely to suffer from CPMC 36,37 and minority adolescents with chronic illnesses have increased rates of stress, compared with nonminority subjects. 38 Gender was not addressed in previous intervention studies, although adolescent female subjects with diabetes tend to report higher levels of diabetes-related stress than do adolescent male subjects.…”
Section: Effects Of Multisystemic Therapy On Diabetes Stressmentioning
confidence: 79%
“…Previous intervention research was conducted with primarily white, middle-class samples and therefore did not address the needs of minority and/or low-income adolescents with diabetes. This is an important gap in the literature, because minority subjects are more likely to suffer from CPMC 36,37 and minority adolescents with chronic illnesses have increased rates of stress, compared with nonminority subjects. 38 Gender was not addressed in previous intervention studies, although adolescent female subjects with diabetes tend to report higher levels of diabetes-related stress than do adolescent male subjects.…”
Section: Effects Of Multisystemic Therapy On Diabetes Stressmentioning
confidence: 79%
“…Racial disparities exist in the treatment and outcomes of children with type 1 diabetes. It has been shown that black children with type 1 diabetes have poorer metabolic control (21)(22)(23)(24). A ninefold increased risk of death was demonstrated for young African Americans with diabetes in Chicago, compared with non-Hispanic white patients with type 1 diabetes over an 8-year period (25).…”
Section: Conclusion -In 1990mentioning
confidence: 99%
“…Although data in childhood are limited, poor metabolic control tracks through adolescence and, in turn, HbA 1c in adolescence is strongly correlated with later adult diabetes-related outcome [10][11][12]. Cross-sectional studies typically show that children of ethnic minorities have higher HbA 1c levels [13][14][15][16]. However, it remains unclear whether this poorer metabolic control is independent of SES, and many of the studies examined selected cohorts that may not be representative of the general population [2,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%